Language Style (Teenage Language) Used By Ustaz Hanan Attaki - Asmaul Husna Husna; Khairunnisa; Ibnu Hajar (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2025)
A muslim master who talks in front of audience and urge us to Allah and changing our mindset in order to act base on Islam principle. In deliver the speech there are some ways in order to attract the listener pay attention. Every Muslim master in Indonesia called by Ustad. They have different rhetorical as their own character to persuade the audience. The use of rhetorical could be seen by the language style they used. One of the popolar Ustad in Teenager environment is Ustad Tengku Hanan Attaki, Lc.It could be His style and rhetorical is relaxive. The material presented and explained by Ustad Hanan Attaki is understandable for teenager. It is likely influence of the teenager language used by Ustad Hanan Attaki. The aim of this research is to analyze how language style used by Ustad Hanan Attaki. The method used is descriptive qualitative. Several episodes of Ustad Hanan Attaki speech were downloaded from YouTube and transcribe. Teenager language utterances were identified and underlined. Data were focused on teenager language base on four categorize; irregular words, tend to abbreviate words, using particle, and the use of foreign language. The result showed that Ustad Hanan Attaki conveys different style. There are the word choice and combine with official and non official language style in four type of teenager language. Which dominant used in his speech is the use of foreign language types. The teenager language used by Ustad Hanan Attaki in his speech success attracts the teenager attention. Keywords: Language Style; Teenager Language Used; Ustad Hanan Attaki